IMPLEMENTASI ARDUINO NANO DAN REED SWITCH UNTUK PERMAINAN EDUKASI HAFALAN DOA ANAK USIA DINI - Vivianti Vivianti; Dwi Ratnawati (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
This study aims to create children's learning media in the form of educational games for dollhouses for daily prayer memorization and life skills education for early childhood.The development method used in making this product is the method of research and development (R And D). The stages of development used in this study consisted of needs analysis, identification of product specifications, product development, product validation, product revisions and trials. The subjects in this study amounted to 6 with the object of daily doll house prayer research. The data collection method used was a questionnaire filled out by trustees. The data analysis technique used in this research is descriptive analysis. The final product is a doll house educational game kit that is integrated with Arduino nano and Reed switch. Products can produce daily prayer sounds and various sound effects that support children's competence in memorizing daily prayers and life skills education. Reed switches are placed in parts of the dollhouse that are set to produce sound. This educational game is presented in a package with Muslim dolls in which there are magnets. When the doll is about a Reed switch, the program on Arduino Nano will give a command to the DFPlayer mini to turn on the sound of prayer and sound effects in accordance with the role activities carried out by children.